Stakeholders of Nature Tourism Management in SPTN Area II Majalengka, Gunung Ciremai National Park - Mita Anindisa; Sambas Basuni; Tutut Sunarminto (Media Konservasi, 2017)
Ecotourism management in Gunung Ciremai National Park is fully managed by third party which are community organizations, state-owned enterprises, and non-governmental organizations. The aims of this research is to identify stakeholders, categorize stakeholders based on interests and influences, also to identify space and determine the level of stakeholder participation. The data obtained using questionnaire, interview, and direct observation were analyzed with stakeholder analysis matrix and the level of stakeholder participation. Fourteen stakeholders involved within the programs based on interests and influences are governmental institutions, cooperations, non-governmental organizations, and community organization with two classifications (key player and crowd). In this management there is no subject and context setter. Most of the stakeholders participate to control level in level of participation. Keywords: ecotourism, interest and influence, level of participation, stakeholder